Web App Voting System in a Philippine State University: An ISO 9241-11 Evaluation - Jessie Richie Naval de los Santos; Michael B. Batan; Giovanni N. de los Santos; Michelle G. de los Santos (Alliance of Health Activists (AloHA), 2020)
Fourth Industrial REvolution offers various technological innovations that contribute significant advantages to the university. The development of the web app voting system (WAVS) in Eastern Visayas State University - Tanauan Campus transformed the voting experience of university students. The study aimed to determine the extent of usability of the WAVS in the Supreme Student Government election. A total of 203 students (voters) served as the respondents using a convenient sampling technique. A descriptive quantitative research design was employed to present the respondents’ views and opinions. The study revealed the system evaluation to be “Excellent” in all factors of usability components on effectiveness (3.50), efficiency (3.43), and user satisfaction (3.42) with a grand mean of 3.45. The WAVS exceeded the users’ requirements on the context of use principles allowing them to perform their tasks efficiently and effectively. The results of the study present an interesting direction of the system implementation across campuses of the university. Developers should consider the mobility of system connectivity using a secured virtual private network (VPN) of the university. Implement security measures on voter’s identity and network firewall encryption. Finally, developers of the system should always consider the usability principles and user requirements in developing an effective and efficient information system.